2009
DOI: 10.1158/1078-0432.ccr-09-0736
|View full text |Cite
|
Sign up to set email alerts
|

Salivary microRNA: Discovery, Characterization, and Clinical Utility for Oral Cancer Detection

Abstract: Purpose: We have previously shown that a transcriptome is found in saliva and subpanels of these mRNAs can be used as oral cancer biomarkers. In this study, we measured the presence of microRNAs (miRNA) in saliva and determined their potential as an additional set of oral cancer biomarkers. Experimental Design: A total of 314 miRNAs were measured using reverse transcriptase-preamplification-quantitative PCR in 12 healthy controls. Degradation pattern of endogenous and exogenous saliva miRNAs were measured at r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
557
1
15

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 754 publications
(600 citation statements)
references
References 36 publications
9
557
1
15
Order By: Relevance
“…Studies conducted by several research groups have confirmed the presence of miRNAs in various body fluids in humans, including serum [49][50][51], plasma [49,50], saliva [52], urine [53], milk [54], cerebrospinal fluid [55] and seminal fluid [56]. In cancer, there is a distinct relationship between the type of biological material and the original location of the neoplasm (e.g.…”
Section: Extracellular Mirnamentioning
confidence: 99%
“…Studies conducted by several research groups have confirmed the presence of miRNAs in various body fluids in humans, including serum [49][50][51], plasma [49,50], saliva [52], urine [53], milk [54], cerebrospinal fluid [55] and seminal fluid [56]. In cancer, there is a distinct relationship between the type of biological material and the original location of the neoplasm (e.g.…”
Section: Extracellular Mirnamentioning
confidence: 99%
“…Subsequent reports have revealed the presence of miRNAs in saliva (Park et al, 2009;Michael et al, 2010) and urine (Hanke et al, 2010). These extracellular miRNAs are stable in the RNase-rich environment because they are enclosed in vesicles, including exosomes, microvesicles, apoptotic bodies, and ectosomes (Lee et al, 2012), or are associated with RNA-binding proteins, including nucleophosmin 1 (Wang K et al, 2010) or high-density lipoprotein (Vickers et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Several miRNAs have been found to be aberrantly expressed in pancreatic cancer tissue, plasma, and serum (19). Moreover, salivary miRNAs have been reported as useful for detecting oral cancer (20,21), Sj€ ogren syndrome (22), and esophageal cancer (23,24). On the basis of these findings, we hypothesized that salivary miRNAs may also possess discriminatory power for pancreatic cancer.…”
Section: Introductionmentioning
confidence: 90%